The use of an ostial stent does not increase the success rate of endoscopic dacryocystorhinostomy. Issue 8 (12th July 2018) - Dinc, M E; Ulusoy, S; Sahin, E; Bozan, N; Avincsal, M O; Tutar, B; Uyar, Y
Abstract: Objective: This prospective, controlled study assessed how placing a stent into a newly formed ostium affects ostial patency, success and complication rates in endoscopic dacryocystorhinostomy patients. Methods: In group 1 (40 eyes of 36 patients), both silicone tube intubation and tube stenting were performed. In group 2 (36 eyes of 34 patients), only silicone tube intubation was performed. Success, operative time and post-surgical complications were investigated two months post-operatively in each group. Results: The success rates were 92.5 per cent and 83.3 per cent for groups 1 and 2 respectively, but the difference was not statistically significant ( p = 0.294). The complication rates also differed between the two groups, but this was again insignificant. Conclusion: Compared with the use of a silicone tube alone, the addition of an ostial stent did not significantly increase the success rate of endoscopic dacryocystorhinostomy.